The Influence of the Implementation of Learning Technology During the Golden Age - M. Abdillah Subhin; Ikhda Esmarasti (Jurnal Pendidikan Nusantara, 2023)
The rapid development of information technology today cannot be avoided, its influence in the world of education. Educators or teachers must fully understand the use of educational technology to avoid accidental damage or educational failure. For this reason, this research examines learning technology as a scientific discipline. This study used the library study method by utilizing the Publish or Perish software as a provider of data information sources needed through several search keywords. The study results show that the importance of attention from many parties to improve the quality of education is accompanied by an increase in the quality of human resources for educators.